Bostäder på vatten i nordliga breddgrader : Möjligheten med etablering av vattenytan i form av flytande bostäder i subarktiskt klimat - Dharsana, Victor; Edberg, Mattias (Luleå tekniska universitet, Arkitektur och vatten, 2017)
Due to the continued advancing of the building industry and the growing number of housing shortages, building on floating components has become an alternative to that on solid land or coastal areas that are geotechnically unsuitable for filling. This can even be done using portable and movable homes. The work is written for Aquashell and the study will describe the possibility of establishing homes on the water surface in Luleå using given floating components. By using suitable building materials and energy supply methods, the building is adapted to Luleå’s sub-arctic climate. The aim of the work is to design flexible housing which is portable and movable that enables settling on the water surface in colder climates in northern latitudes by the use of suitable materials and building modules. Firstly, a literature study was conducted on the subject together with studies in the form of interviews and location visits. Then a program was created with requirements for the building. After that a design proposal was made containing appropriate material choices which were then chosen to be visualized in Luleå’s Norra Hamn as a possible residential area. The floating homes are adapted to the climate and designed with respect to the surrounding environment in order to optimally take advantage of the scenic views in the area. The hope of the work is to demonstrate the possibility for housing on water by use of floating buildings even in sub-arctic climates. The work can also provide a potential solution in response to the ever-increasing shortage of housing.